Sunscreen-induced expression and identification of photosensitive marker proteins in human keratinocytes under UV radiation. (July 2019) - Amar, Saroj Kumar; Srivastav, Ajeet K; Dubey, Divya; Chopra, Deepti; Singh, Jyoti; Mujtaba, Syed Faiz
Solar ultraviolet (UV) radiation is the main factor of photocarcinogenesis, photoaging, and photosensitivity; thus protection from biological damaging UV radiation is a concern. Sunscreens containing UV filters are the most preferred means of photoprotection but the safety and efficacy of UV filters are in question. Benzophenone (BP) and its derivatives, namely, benzophenone 1 (BP1), is commonly used in sunscreens as a UV blocker. The aim of this study was to assess the effects of BP and BP1 on the differential expression of proteins in human keratinocytes (HaCaT cells) under exposure to ultraviolet A radiation. Photosensitive proteins were screened from HaCaT cells by two-dimensional (2-D) gel electrophoresis, and identification of these differentially expressed proteins was performed by matrix-assisted laser desorption/ionization-time-of-flight (MALDI-TOF)/TOF mass spectrometry. Protein identification was performed using the search program MASCOT and a database made of SUMO and GhJMJ12 amino acid sequences. Our results showed that the proteins involved directly or indirectly in apoptosis are 70 kDa heat shock protein, long-chain specific acyl-CoA dehydrogenase, serine/threonine-protein kinase, and FAM78A protein, which were upregulated in comparison to control HaCaT cells. The expressions of binding immunoglobulin protein, podocalyxin-like protein, actin, cytoplasmic, and calreticulin precursors were downregulated. The altered protein expression indicated that cell growth arrest and apoptosis were potential mechanisms of cytotoxicity and genotoxicity of BPs. The results of 2-D gel electrophoresis followed by mass spectrometry showed expression of novel proteins involved in promoting or initiating apoptotic pathways. Hence, we conclude that BPs should be avoided as a UV blocker from sunscreens because of its potential to promote apoptotic proteins in human skin keratinocytes.